Analysis of The Arabic Language Textbook for the Islamic Middle School for the Seventh Grade based on Multiple Intelligences - Rifa'i, Arwan (Naatiq: Journal of Arabic Education, 2024)
This research aims to analyse the 2013 curriculum Arabic language textbook based on the theory of multiple intelligences. The research uses a qualitative descriptive approach with content analysis method for the 7th grade student textbook of Islamic junior high school under the 2013 curriculum with the topic "Let's Understand Arabic". The purpose of this study is to identify the multiple intelligences present in the student textbook, determine the unit of analysis, determine the sample, prepare a coding guide, collect data, analyze the harmony between the book and the concept of multiple intelligences, describe the results of the analysis based on the multiple intelligence concept, draw conclusions and provide recommendations. The study revealed that the 7th grade student textbook under the topic "Let's Understand Arabic" did not adequately facilitate the development of students' multiple intelligences, as the distribution of multiple intelligences in the book is uneven. The most prevalent intelligences in the book are linguistic intelligence at 31% and visual-spatial intelligence at 31%, followed by logical-mathematical intelligence at 26%, while the least represented intelligences are bodily-kinesthetics and interpersonal intelligences at 6% each. To enhance these intelligences, instructional materials on songs, rhythms, rhythmic patterns, etc. can be added, and discussion on symbolic behaviour and dasa dharma behaviour can be expanded. Thus, developing instructional materials in student textbooks is an important step for authors or writers in maximizing the development of students' intelligences.